Determinants of Formal-Informal Labour Mobility in Indonesia: A Longitudinal Analysis Using World Bank Data - Nurlyna Nurlyna; Ermalina Ermalina (Journal of Innovative and Creativity, 2026)
Indonesia's structural labour transformation faces a unique paradox: stable economic growth has not fully succeeded in accelerating the transition of labour from the informal to the formal sector. This study addresses the urgent need to understand the determinants of worker mobility between sectors, which has been a missing link in the formulation of national labour policies. The objective of this study is to identify the factors that determine formal-informal mobility and analyze the long-term dynamics of Indonesia's structural labour transformation. The method used is a longitudinal approach, analyzing World Bank data from 2000 to 2023 through panel regression and time series analysis. An econometric model was developed to quantify the influence of macroeconomic variables, labour characteristics, and policies on sectoral mobility patterns. The findings reveal a consistent trend of formalization, with the formal-informal ratio increasing from 0.49 to 0.96, despite the strong persistence of the informal sector (ADF p-value 0.1225).. Economic growth shows limited correlation with labour mobility, while structural factors and policies have a more significant influence. The regression model produces 95.6% explanatory power with the lagged employment variable as the most dominant determinant (coefficient of 0.790). The limitations of the study mainly lie in the uneven availability of sectoral data and the observation period, which does not yet cover the full impact of the COVID-19 pandemic. Nevertheless, these findings provide a valuable empirical basis for the formulation of more evidence-based and contextual labour policies. The study recommends an integrated policy approach to accelerate the transformation towards an inclusive and sustainable formal economy